Reading comprehension and learning in language and communication: Analysis by literal, inferential and criterion levels in students of the 1st cycle of the National Autonomous University of Huanta, 2021 - Oré Cabrera, Fidencio (2026)
The purpose of the research was to establish the correlation between reading comprehension and learning in the subject of Language and Communication in first-year students at the National Autonomous University of Huanta during 2021. This research was classified as basic, descriptive-correlational research, adopting a quantitative approach, a deductive method, and a non-experimental cross-sectional design. The study population consisted of 100 students, who were given reading comprehension and learning questionnaires. The findings revealed a significant and positive correlation between reading comprehension and learning in the subject (p = 0.000 < 0.05; r = 0.718), which facilitated the rejection of the null hypothesis. Additionally, a significant and positive correlation was identified between the literal level and learning (p = 0.002 < 0.05; Rho = 0.375), between the inferential level and learning (p = 0.000 < 0.05; Rho = 0.676), and between the criterion level and learning (p = 0.000 < 0.05; Rho = 0.777). In all instances, these findings corroborate the presence of a positive association and the subsequent rejection of the null hypothesis. In conclusion, students who achieve an appropriate criterion level in reading comprehension—by discerning the content of a text, distinguishing facts from opinions, and analyzing the author's intent—achieve more robust learning in the discipline of Language and Communication.